2021
DOI: 10.1021/acsami.1c00974
|View full text |Cite
|
Sign up to set email alerts
|

Layered Double Hydroxide Quantum Dots for Use in a Bifunctional Separator of Lithium–Sulfur Batteries

Abstract: Functional separators, which are chemically modified and coated with nanostructured materials, are considered an effective and economical approach to suppressing the shuttle effect of lithium polysulfide (LiPS) and promoting the conversion kinetics of sulfur cathodes. Herein, we report cobalt−aluminum-layered double hydroxide quantum dots (LDH-QDs) deposited with nitrogen-doped graphene (NG) as a bifunctional separator for lithium−sulfur batteries (LSBs). The mesoporous LDH-QDs/ NG hybrids possess abundant act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…The high‐resolution C 1s XPS spectra presents four characteristic peaks at 284.5, 286.1, 287.3 and 288.6 eV, which are assigned to carbon in C=C, C‐O, C‐N, and O‐C=O bonds, respectively (Figure 3C). 27,48‐49 These results indicate that the oxygen‐containing functional groups of NRGO are associated with the formation of Re‐O bonds between ReS 2 and NRGO, leading to the vertical growth of ReS 2 nanosheets onto the NRGO surface for the construction of 3D hierarchical architectures 29 . Moreover, the high‐resolution N 1s XPS spectra are fitted and divided into three peaks (Figure 3D), where the peak at 398.2 eV corresponds to the pyridinic N and the peaks at 399.7 and 401.4 eV are assigned to pyrrolic N and graphitic N, respectively 50 .…”
Section: Resultsmentioning
confidence: 91%
“…The high‐resolution C 1s XPS spectra presents four characteristic peaks at 284.5, 286.1, 287.3 and 288.6 eV, which are assigned to carbon in C=C, C‐O, C‐N, and O‐C=O bonds, respectively (Figure 3C). 27,48‐49 These results indicate that the oxygen‐containing functional groups of NRGO are associated with the formation of Re‐O bonds between ReS 2 and NRGO, leading to the vertical growth of ReS 2 nanosheets onto the NRGO surface for the construction of 3D hierarchical architectures 29 . Moreover, the high‐resolution N 1s XPS spectra are fitted and divided into three peaks (Figure 3D), where the peak at 398.2 eV corresponds to the pyridinic N and the peaks at 399.7 and 401.4 eV are assigned to pyrrolic N and graphitic N, respectively 50 .…”
Section: Resultsmentioning
confidence: 91%
“…XPS spectra of the NiFe‐LDH@OCNT before and after the adsorption experiment of Li 2 S 6 were analyzed to understand the LiPSs inhibition mechanism 23,24 . In Figure 4C, the Fe 2p 3/2 peaks of the original NiFe‐LDH@OCNT located at 711.29, 713.19, and 714.13 eV were attributed to the characteristic peaks of Fe 2+ , Fe 3+ , and shakeup satellites (abbreviated as “sat.”), respectively 25‐29 . For NiFe‐LDH@OCNT, the peaks of Fe 2+ and Fe 3+ shifted to 711.06 and 712.95 eV, respectively, after the adsorption of Li 2 S 6 .…”
Section: Resultsmentioning
confidence: 98%
“…"), respectively. [25][26][27][28][29] For NiFe-LDH@OCNT, the peaks of Fe 2+ and Fe 3+ shifted to 711.06 and 712.95 eV, respectively, after the adsorption of Li 2 S 6 . Figure 4D shows that the Ni 2p 3/2 peaks of the original NiFe-LDH@OCNT were detected at 856.87, 858.89, and 862.64 eV, which were attributed to Ni 2+ , Ni 3+ , and sat., respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the control study with only the MWCNT coated PP separator showed a lower initial specific capacity of 1126.1 mA h g −1 , accompanied by comparatively faster capacity decay with only 480 mA h g −1 specific capacity retention over 500 cycles. Recently, Liu et al 235 demonstrated a Co–Al layered double hydroxide (LDH) QDs@N-doped graphene (NG) modified PP separator in a Li–S battery. The Co 2+ and hydroxide groups of LDH offer strong chemical interaction with LiPSs to prevent polysulfide shuttling, simultaneously accelerating the redox reaction kinetics.…”
Section: Quantum Dot Based Nanocomposite Electrodes For Lithium Metal Batteriesmentioning
confidence: 99%